REPRESENTASI LOYALITAS YANG TERKANDUNG DALAM MUSIC VIDEO BTS “WE ARE BULLETPROOF: THE ETERNAL” - Kamelia Hanashofi Asih; Muhammad Adi Sukma Nalendra (JURNAL RUPA MATRA, 2022)
This research is about the meaning of visualization in the music video "We Are Bulletproof: The Eternal" by BTS. The purpose of this study is to find out the meaning of loyalty values contained in the video clip. The study used Roland Barthes' semiotic analysis of two stages, namely denotation and connotation. The results of this study found that the music video "We Are Bulletproof: The Eternal" tells the career journey of South Korean boyband BTS, to achieve success as it is today. Of course, this success is not spared from the influence of fans who participate in providing support to BTS. The music video is also an offering from BTS as a gift ahead of BTS's debut day. BTS wants to reveal that without fans, BTS will not consist of 7 people who became as successful as they are today